Roles for the long non-coding RNA Pax6os1/PAX6-AS1 in pancreatic beta cell function - Livia Lopez-Noriega; Rebecca Callingham; Aida Martinez-Sánchez; Sameena Nawaz; Grazia Pizza; Nejc Haberman; Nevena Cvetesic; Marie-Sophie Nguyen-Tu; Boris Lenhard; Piero Marchetti; Lorenzo Piemonti; Eelco de Koning; et al. (iScience)
Summary: Long non-coding RNAs (lncRNAs) are emerging as crucial regulators of beta cell function. Here, we show that an lncRNA-transcribed antisense to Pax6, annotated as Pax6os1/PAX6-AS1, was upregulated by high glucose concentrations in human as well as murine beta cell lines and islets. Elevated expression was also observed in islets from mice on a high-fat diet and patients with type 2 diabetes. Silencing Pax6os1/PAX6-AS1 in MIN6 or EndoC-βH1 cells increased several beta cell signature genes’ expression. Pax6os1/PAX6-AS1 was shown to bind to EIF3D, indicating a role in translation of specific mRNAs, as well as histones H3 and H4, suggesting a role in histone modifications. Important interspecies differences were found, with a stronger phenotype in humans. Only female Pax6os1 null mice fed a high-fat diet showed slightly enhanced glucose clearance. In contrast, silencing PAX6-AS1 in human islets enhanced glucose-stimulated insulin secretion and increased calcium dynamics, whereas overexpression of the lncRNA resulted in the opposite phenotype.